Sand Problem Handling Strategy On Well Ar-02 With Hydraulic Pumping Unit - Ayu Regita Pramesti; Nur Suhascaryo; Boni Swadesi (Journal of Petroleum and Geothermal Technology, 2022)
AR-02 well is one of the oil production wells located in Structure X. This well is produced using the Hydraulic Pumping Unit (HPU) method due to low reservoir pressure as a result of the reduced production capacity of the Y Field formation. In addition, this well has sand problems because the fluid production rate of 96 bfpd exceeds the critical sand flow rate of 66.81 bfpd. The physical properties of reservoir rocks do not cause sand problems because they have a cementation factor of highly cemented (m = 1.99), relatively small clay content (5.4%), compact rock (∆t = 54.16 s/ft), and compact as well as stable formation rock (G/Cb = 14.85x1012 psi2). In solving the sand problem in the AR-02 Well, the Gravel Pack and screen were installed. The correct Gravel size according to the Saucier method is 0.035 inch and the correct screen size according to the Coberly & Wagner, Tauch & Corley, and H. J. Ayre methods is 0.016 inch. The value (G-S) ratio indicates that the selection of Gravel and screen sizes is correct (stable), namely the value (G-S) ratio is at number 5. Redesign of the production scheme due to the installation of the Gravel Pack with the use of HPU pumps at the same setting produces; P due to Gravel installation 40 psi, qfluid after Gravel installation 90 bfpd (previously 95 bfpd), PI after Gravel installation 0.188 (previously 0.198), Min allowable stress 8991.56 psi, Max allowable stress 23420.64 psi, Total stretch 55.42 inch, Over travel 0.391 inch, Plunger stroke 94.97 inch, and Pump Displacement 135.65 bfpd.